Improvement of Transmission Line Power Transfer Capability, Case Study - Abu-Siada, Ahmed; Karunar, C. (Wireilla Scientific Publications, 2012)
This paper investigates different approaches to improve the power transfer capability (PTC) of transmission lines. Study was performed on the Eastern Gold Fields (EGF) area of the Western Power network in Western Australia where power transfer to this area is currently enhanced using four saturable reactor types static var Compensators (SR SVCs) installed in this region. These SR SVCs have reached to the end of operational life and they are scheduled for replacement by different dynamic reactive power devices such as Static Synchronous Compensators (STATCOMs) or Thyristor Controlled SVCs (TSVCs). Another proposed option to enhance the PTC to this area is by upgrading the 220 kV transmission line to 275 kV transmission line and / or using series capacitor compensation. This paper introduces technical and economical study for the aforementioned options and suggests a reliable and cost effective approach to improve the PTC to EGF area.